Strategi Komunikasi Kepala Sekolah dalam Meningkatkan Kualitas Kerja Guru di Min 1 Medan - Khoirul Saleh Harahap; Akbar Tanjung; Ali Sanusi Rambe; Mesiono Mesiono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to explore and analyze the communication strategies implemented by school principals to improve the quality of teacher work at Madrasah Ibtidaiyah Negeri (MIN) 1 Medan City. The quality of teacher work significantly impacts student achievement and the effectiveness of the learning process. This research method uses a qualitative approach with in-depth interviews with school principals, teachers, and related parties. Data was also collected through observations in the school environment and analysis of associated documents. Data analysis used content analysis techniques to identify patterns and themes from interviews and observations. The research results show that the school principal at MIN 1 Medan City applies various effective communication strategies to develop teacher work quality. In conclusion, this strategy involves open and transparent communication, regularly conveying the school's vision and mission, and providing constructive feedback to teachers. School principals also utilize regular meetings, training, and other means of communication to build collaboration and a spirit of working together. Keywords: Communication, Communication Strategy, School Principal, Teacher Work